DNA methylation patterns in human iPSC-derived sensory neuronal differentiation - Soneela Ankam; Amandine Rovini; Saurabh Baheti; Ron Hrstka; Yanhong Wu; Kiley Schmidt; Hailong Wang; Nicolas Madigan; Lena-Sophie Koenig; Kimberly Stelzig; Zachary Resch; Christopher J. Klein; et al. (Epigenetics, 2019)
Sensory neurons of the peripheral nervous system are critical in health and disease. Sensory neurons derived from induced pluripotent stem (iPS) cells are now being used increasingly for in vitro models of neuropathy, pain, and neurotoxicity. DNA methylation is critical for neurodevelopment and has been implicated in many neuronal diseases, but has not been examined in iPS-derived sensory neurons. In order to better characterize the iPS-derived sensory neuron model, we have undertaken a genome-wide DNA methylation study on the cells from human iPS to iPS-derived sensory neurons during differentiation through reduced representation and bisulfite sequencing. We report decreasing DNA methylation with iPS-derived sensory neuronal differentiation that is reflected in increasing numbers and proportions of hypomethylated individual CpGs and regions, as well as lowered DNMT3b expression. Furthermore, genes with changes in DNA methylation near their TSS suggest key pathways that may be involved in iPS-derived sensory neuronal differentiation. These findings provide insights into sensory neuronal differentiation and can be used for further in vitro modelling of disease states.